Patients with primary thrombophilia on anticoagulation face increased mortality, thromboembolic events, and neurologic complications after laminectomy: a propensity-matched analysis - Syed, Naasik; Zaidi, Zuhair; Wahid, Muaz; Desai, Ronak (International Journal of Research in Orthopaedics, 2026)
Background: Inherited thrombophilias are known risk factors for venous thromboembolism (VTE). The impact of thrombophilia on spine surgery outcomes, especially laminectomy, remains poorly defined, particularly in the context of chronic anticoagulation. Methods: Using the TriNetX Research Network, we conducted a retrospective cohort study of adult patients undergoing laminectomy between 2004–2025. Patients with primary thrombophilia on ≥6 months of anticoagulation prior to surgery were identified and propensity score–matched 1:1 to controls without thrombophilia or anticoagulation. Outcomes assessed at 90 days and 1 year included mortality, VTE, systemic complications, neurologic deficits, and hospitalizations. Results: A total of 3,812 matched patients were analyzed. At 90 days, thrombophilia patients had significantly higher rates of mortality, deep vein thrombosis (DVT), sepsis, and hospitalizations. At 1 year, rates of mortality remained elevated, as did DVT, hospitalizations, and new or worsening neurologic deficits. Other systemic and surgical complications were not significantly different. Conclusion: Patients with inherited thrombophilia on anticoagulation face substantially higher risks of morbidity and mortality following laminectomy. These findings underscore the need for careful perioperative anticoagulation strategies and individualized risk assessment in this high-risk surgical population.